2001
DOI: 10.1177/03635465010290010801
|View full text |Cite
|
Sign up to set email alerts
|

Lower-Limb Function among Former Elite Male Athletes

Abstract: To determine the relationship between previous lower-limb loading and current self-reported hip and knee disability, we sent a questionnaire to 1321 former elite male athletes who had represented Finland between 1920 and 1965 in international competitions and to 814 control subjects who had been classified as healthy at the age of 20. After adjustment for age, body mass index, and occupational group, the odds ratios of hip disability in the athletes compared with control subjects were 0.35 in endurance athlete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
1
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(112 citation statements)
references
References 27 publications
9
94
1
8
Order By: Relevance
“…In 3 studies, 27,28,31 the prevalence of OA was lower in those with mandatory national military service requirements than in controls; however, the prevalence of OA was significantly lower in only 1 of these studies. 31 Conversely, investigators in 5 studies [27][28][29][30]32 reported a higher prevalence of OA in those with mandatory national military service requirements compared with controls, but again, the prevalence of OA was significantly higher in only 1 of these studies. 30 Authors of 2 studies 37,28 found a higher prevalence for some OA outcomes and a lower prevalence for others.…”
Section: Mandatory National Military Service and Oamentioning
confidence: 97%
See 1 more Smart Citation
“…In 3 studies, 27,28,31 the prevalence of OA was lower in those with mandatory national military service requirements than in controls; however, the prevalence of OA was significantly lower in only 1 of these studies. 31 Conversely, investigators in 5 studies [27][28][29][30]32 reported a higher prevalence of OA in those with mandatory national military service requirements compared with controls, but again, the prevalence of OA was significantly higher in only 1 of these studies. 30 Authors of 2 studies 37,28 found a higher prevalence for some OA outcomes and a lower prevalence for others.…”
Section: Mandatory National Military Service and Oamentioning
confidence: 97%
“…21 The remaining researchers either examined the incidence or prevalence of OA in active-duty or veteran military populations [22][23][24][25][26] or examined the prevalence of OA in European countries where national military service is mandatory. [27][28][29][30][31][32] Two studies examined OA incidence rates in active-duty military populations 22,23 and compared them with published reference rates in the general population. 3,35,36 No studies were identified that examined OA incidence or prevalence in other tactical athlete populations (eg, law enforcement, first responders).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…11 Team sports, such as soccer, 23,51 Australian football, 20 hockey, and basketball 51 have been linked to a higher risk of knee disability. Running for fitness and exercise has become a popular activity in the United States.…”
Section: Sport-specific Injuriesmentioning
confidence: 99%
“…Considering the important contingent of players, soccer accounts for the highest indices of sports-related musculoskeletal disorders (MSDs) 3 . Because it is a competitive sport, the high risk of injuries worries coaches, trainers and players in all categories as it disrupts the evolutionary processes and systematic adjustments imposed by training 4,5 . From a socioeconomic standpoint, the high indices of sports injuries (SI) results in financial losses to teams and sponsors, including additional health costs and temporary inaction that may result in permanent functional deficits³.…”
Section: Introductionmentioning
confidence: 99%
“…From a socioeconomic standpoint, the high indices of sports injuries (SI) results in financial losses to teams and sponsors, including additional health costs and temporary inaction that may result in permanent functional deficits³. Hence it is important to highlight that soccer is marked by physical contact and performance of specific sports actions such as running, jumping, landings, acceleration, slowdown, abrupt changes of direction, kicks and tramping 1,5 . Features such as resistance, velocity, agility, flexibility and strength are essential requirements to the full exercise of soccer 1 .…”
Section: Introductionmentioning
confidence: 99%